Pengaruh Pemberian Dosis Pupuk Kandang Ayam Petelur Dan NPK Mutiara 16:16:16 Terhadap Pertumbuhan Tanaman Lai Mahakam (Durio Kutejensis Hassk Becc) Belum Menghasilkan - Zainudin Zainudin (Agrifarm : Jurnal Ilmu Pertanian, 2016)
This study aims to determine the dose of laying hens manure and fertilizer NPK 16:16:16 Mutiara right and the interaction between the dosing laying hen manure and NPK 16:16:16 pearls in improving plant growth Lai Mahakam immature. The study was conducted over four months, from May to September 2015 starting from land clearance, maintenance of plants, to capture data. This research was conducted at Badak Mekar village, Muara Badak, Regency. The design of the study is a randomized block design factorial 3 x 3 with three replications. The first factor is the dose of chicken manure (K) consisting of 3 levels: K0 (control), K1 (10 kg / plant) and K2 (20 kg / plant). The second factor is the dose of fertilizer NPK 16:16:16 Mutiara (M) comprises 3 levels: M0 (Control), M1 (200 g / plant) and M2 (400 g / plant). The treatment dose of chicken manure had no significant effect on all parameters of observation. Treatment fertilizer NPK 16:16:16 Mutiara very significant effect on all parameters of observation. The best treatment for an average plant height increment of age 90 days after treatment was achieved by treatment M1 (200 g / plant) is 15.54 cm while the lowest treatment was achieved by treatment M0 (control) is 7.03 cm. Interaction between chicken manure and NPK 16:16:16 Mutiara not significantly affected all parameters of observation.